2015
DOI: 10.1186/s12889-015-2673-6
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of dental caries among young Aboriginal children in New South Wales, Australia: a cross-sectional study

Abstract: BackgroundLimited research has been undertaken in Australia to assess the dental status of pre-school Aboriginal children. This cross-sectional study records the number of decayed, missing and filled teeth (dmft) and surfaces (dmfs) of pre-school Aboriginal children living in different locations in New South Wales (NSW), Australia.MethodsA convenience sample of young children from seven Aboriginal communities in rural, remote and metropolitan areas of NSW, was recruited. One calibrated examiner recorded the dm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(51 citation statements)
references
References 27 publications
3
44
0
4
Order By: Relevance
“…There is also no available population data on the prevalence rates of ECC among preschool Aboriginal children in NSW . The only comparable research has shown that nearly half the Aboriginal children under 6 years across rural and metropolitan NSW had dental caries . This suggests that there may be a disconnect among Aboriginal parents in this study regarding their perceived oral health concerns about the child and actual issues.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…There is also no available population data on the prevalence rates of ECC among preschool Aboriginal children in NSW . The only comparable research has shown that nearly half the Aboriginal children under 6 years across rural and metropolitan NSW had dental caries . This suggests that there may be a disconnect among Aboriginal parents in this study regarding their perceived oral health concerns about the child and actual issues.…”
Section: Discussionmentioning
confidence: 73%
“…The Gudaga study describes the oral health behaviours and fluid consumption practices of young urban Aboriginal children of the Tharawal community in south‐western Sydney. Although the study data presented are slightly dated (2007‐2012), the findings provide a valuable contribution in this area as there is currently limited information on the oral health practices of urban Aboriginal children in Australia, particularly for the early childhood period . Most of the published literature on Aboriginal children under 5 years of age focuses on their uptake of dental services and hospitalisation rates for dental procedures during this period …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations